Genome Features and Secondary Metabolites Biosynthetic Potential of the Class Ktedonobacteria - Zheng, Yu; Saitou, Ayana; Wang, Chiung-Mei; Toyoda, Atsushi; Minakuchi, Yohei; Sekiguchi, Yuji; Ueda, Kenji; Takano, Hideaki; Sakai, Yasuteru; Abe, Keietsu; Yokota, Akira; Yabe, Shuhei (Frontiers in Microbiology, 2019)
The prevalence of antibiotic resistance and the decrease in novel antibiotic discovery in recent years necessitates the identification of potentially novel microbial resources to produce natural products. Ktedonobacteria, a class of deeply branched bacterial lineage in the ancient phylum Chloroflexi, are ubiquitous in terrestrial environments and characterized by their large genome size and complex life cycle. These characteristics indicate Ktedonobacteria as a potential active producer of bioactive compounds. In this study, we observed the existence of a putative “megaplasmid”, multiple copies of ribosomal RNA operons, and high ratio of hypothetical proteins with unknown functions in the class Ktedonobacteria. Furthermore, a total of 104 antiSMASH-predicted putative biosynthetic gene clusters (BGCs) for secondary metabolites with high novelty and diversity were identified in nine Ktedonobacteria genomes. Our investigation of domain composition and organization of the nonribosomal peptide synthetase and polyketide synthase BGCs further supports the concept that class Ktedonobacteria may produce compounds structurally different from known natural products. Furthermore, screening of bioactive compounds from representative Ktedonobacteria strains resulted in the identification of broad antimicrobial activities against both gram-positive and gram-negative tested bacterial strains. Based on these findings, we propose the ancient, ubiquitous, and spore-forming Ktedonobacteria as a versatile and promising microbial resource for natural product discovery.